Psychological symptoms among parents of adolescents with anorexia nervosa: a descriptive examination of their presence and role in treatment outcome. Issue 4 (23rd July 2015) - Forsberg, Sarah; Darcy, Alison; Bryson, Susan W.; Arnow, Katherine D.; Datta, Nandini; Le Grange, Daniel; Lock, James
Abstract : Parent psychological symptoms were examined in a randomized controlled trial comparing family‐based treatment (FBT) and adolescent‐focused therapy (AFT) for anorexia nervosa, and were explored across treatments and in relation to treatment outcomes. Moderator and mediator analyses were completed with parent symptoms as predictors and weight remission and recovery status as outcome variables. Few parents had clinically significant symptoms at presentation. At the end of treatment (EOT), parents had decreased psychological symptoms in both treatment arms. Higher baseline levels of overall maternal symptomology and improvement in maternal symptomology were non‐specific predictors of adolescent weight outcome at EOT and 12‐month follow up. Mothers with few to no depressive symptoms had children with the greatest improvement in weight at EOT when assigned to family treatment. In sum, parent symptoms did not appear to negatively impact on the treatment outcome among adolescents with anorexia nervosa. Practitioner points: Parent involvement is considered best practice in the treatment of adolescent anorexia nervosa (AN). There are limited data on psychological symptoms among parents of individuals with AN, and their impact on treatment outcome. Among a sample of adolescents with AN, parent psychological symptoms improved across individual and family treatment. Future studies may wish to explore the impact of maternal depression on refeeding efforts in family‐based treatment.